2016
DOI: 10.1080/10439463.2016.1151881
|View full text |Cite
|
Sign up to set email alerts
|

A small constellation: risk factors informing police perceptions of domestic abuse

Abstract: Police in the United States (US) and the United Kingdom (UK) now routinely use risk assessment tools to identify common risk factors for re-abuse and lethality when responding to domestic abuse. Nevertheless, little is known about the extent to which officers understand and perceive the importance of factors commonly included on risk assessment tools for predicting future abuse. This study attempts to shed some light into this area of research by exploring the responses of 720 British and American police offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 35 publications
8
66
0
1
Order By: Relevance
“…Belfrage & Strand, 2012;Belfrage et al, 2012a;Storey, Kropp, Hart, Belfrage & Strand, 2014); police officers' decision making in the risk assessment and management procedure (e.g. Robinson, Pinchevsky & Guthrie, 2016;Trujillo & Ross, 2008), and the inter-rater reliability/consistency of police officers risk assessments (e.g. Sebire & Barling, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Belfrage & Strand, 2012;Belfrage et al, 2012a;Storey, Kropp, Hart, Belfrage & Strand, 2014); police officers' decision making in the risk assessment and management procedure (e.g. Robinson, Pinchevsky & Guthrie, 2016;Trujillo & Ross, 2008), and the inter-rater reliability/consistency of police officers risk assessments (e.g. Sebire & Barling, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, Trujillo and Ross (2008) found police officers to be biased in their summarized IPV risk assessments. They also found, in line with Robinson et al (2016) that police officers tend to put the greatest emphasis on a small number of risk factors in their assessments. This suggests that the poor predictive accuracy might also be due to the quality of the summarized risk assessments themselves, and thus not merely a result of the effect of interventions.…”
Section: Introductionmentioning
confidence: 56%
“…Belfrage & Strand, 2012;Belfrage et al, 2012a;Storey, Kropp, Hart, Belfrage & Strand, 2014); police officers' decision making in the risk assessment and management procedure (e.g. Robinson, Pinchevsky & Guthrie, 2016;Trujillo & Ross, 2008), and the inter-rater reliability/consistency of police officers risk assessments (e.g. Sebire & Barling, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that police officers tend to prioritize indicators of physical violence when assessing risk, and in particular whether there has been injurious violence during the incident to which they have been deployed (Robinson et al, 2015(Robinson et al, , 2016. A major inspection of the police response to domestic violence in England and…”
Section: Discussionmentioning
confidence: 99%